Implementing group visits for opioid use disorder: A case series. Issue 2 (2nd April 2020) - Sokol, Randi; Albanese, Mark; Albanese, Chiara; Coste, Gerard; Grossman, Ellie; Morrill, Diana; Roll, David; Sobieszczyk, Amy; Schuman-Olivier, Zev
Abstract: Background: Group-based models of Office-Based Opioid Treatment with buprenorphine-naloxone (B/N) are increasingly being implemented in clinical practice to increase access to care and provide additional therapeutic benefits. While previous studies reported these Group-Based Opioid Treatment (GBOT) models are feasible for providers and acceptable to patients, there has been no literature to help providers with the more practical aspects of how to create and maintain GBOT in different outpatient settings. Case series: We present 4 cases of GBOT implementation across a large academic health care system, highlighting various potential approaches for providers who seek to implement GBOT and demonstrate "success" based on feasibility and sustainability of these models. For each case, we describe the pros and cons and detail the personnel and resources involved, patient mix and group format, workflow logistics, monitoring and management, and sustainability components. Discussion: The implementation details illustrate that there is no one-size-fits-all approach, although feasibility is commonly supported by a team-based, patient-centered medical home. This approach includes the capacity for referral to higher levels of mental health and addiction support services and is bolstered by ongoing provider communication and shared resources across the health system. Future research identifying the core and malleable components to implementation, their evidence base, and how they might be influenced by site-specific resources, culture, and other contextual factors can help providers better understand how to implement a GBOT model in their unique clinical environment.